"Загублена Ема" – символ утраченого - Кавасіма Сюїті (Народна творчість та етнографія, 2009)
"Forgotten Ema» is a paper tablet with an image on of the lost thing in the sea it, which was brought to the Shinto temple as the offering to a Dragon-God.
The region of distribution of such tablets is described in the work, as well as what exactly the Japanese depicted on die sacred tablets, in what temples they brought such tablets and from what these tablets were made are analyzed. The beliefs of fishermen related to the successful fishing are described. Also the purpose of the article was to acquaint readers with the role of shamans in the life of fishermen and the relation of the Japanese to the sea.